2018
DOI: 10.1007/s10681-018-2115-5
|View full text |Cite
|
Sign up to set email alerts
|

Technology generation to dissemination: lessons learned from the tef improvement project

Abstract: Indigenous crops also known as orphan crops are key contributors to food security, which is becoming increasingly vulnerable with the current trend of population growth and climate change. They have the major advantage that they fit well into the general socio-economic and ecological context of developing world agriculture. However, most indigenous crops did not benefit from the Green Revolution, which dramatically increased the yield of major crops such as wheat and rice. Here, we describe the Tef Improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
(20 reference statements)
0
20
0
Order By: Relevance
“…Research on tef genomics started very recently (Girma et al 2014;Cannarozzi et al 2018a). The first whole-genome sequence of tef contains 672 Mbp representing 87% of the total tef genome size (Cannarozzi et al 2014).…”
Section: Omics Studies On Tefmentioning
confidence: 99%
“…Research on tef genomics started very recently (Girma et al 2014;Cannarozzi et al 2018a). The first whole-genome sequence of tef contains 672 Mbp representing 87% of the total tef genome size (Cannarozzi et al 2014).…”
Section: Omics Studies On Tefmentioning
confidence: 99%
“…However, due to the high value of the tef straw as a livestock feed, breeding for a significant reduction in plant height might have little acceptance by the farmers (Yami, 2013). In order to be successful tef improvement projects must also take into account the agroecology and socioeconomic conditions of the region (Cannarozzi et al, 2018) and as such alternatives to shortening the stem must be found. The lower lodging varieties had a lower self-weight moment which makes them less likely to bend under their own weight.…”
Section: Discussionmentioning
confidence: 99%
“…In order to be successful, tef improvement projects must also take into account the agroecology and socioeconomic conditions of the region (Cannarozzi et al, 2018). We, therefore, compare morphological traits and measure mechanical properties in five different tef genotypes to investigate alternatives to breed for shorter stems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The project aims at improving the orphan cereal crop tef and it is hosted at the Institute of Plant Sciences at the University of Bern in Switzerland. The project employs key genetic and genomic tools (Esfeld et al 2013b;Girma et al 2018) and collaborates with the National Tef Improvement Program in Ethiopia to develop tef varieties with desirable traits (Cannarozzi et al 2018a;Kebede et al 2018). The group led an international group of scientists which resulted in the genome sequence of the draft genome of tef (Cannarozzi et al 2014).…”
Section: Tef Improvement Projectmentioning
confidence: 99%